Impact of Acute Myocardial Injury on Short‐ and Long‐Term Outcomes in Patients With Primary Intracerebral Hemorrhage - Shenghui Ma; Jiawen Li; Qi Kong; Zhiming Xu; Haojie Wu; Yujia Jin; Xianghua Ye; Dong Luo; Lusha Tong; Feng Gao (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Myocardial injury is common after brain injury; however, few studies have reported serial cardiac troponin (cTn) measurements to distinguish whether the myocardial injury is acute or chronic. The fourth Universal Definition of Myocardial Infarction introduced for the first time the criteria for acute myocardial injury (AMI). We aimed to investigate the prevalence and prognostic implications of AMI in primary intracerebral hemorrhage. Methods and Results We retrospectively analyzed patients with primary intracerebral hemorrhage within 48 hours after symptom onset. All patients included had at least 2 cTn measurements: 1 obtained at the time of emergency admission and at least 1 more within the first 2 days of hospitalization. AMI was defined as an elevated cTn above the upper‐reference limit (14 ng/L) along with a rise/fall >20%. Patients were followed for up to 5 years. Outcomes included major adverse cardiac events (MACEs; a composite of vascular death, nonfatal coronary events, and nonfatal stroke) and 90‐day unfavorable outcomes (modified Rankin scale score ≥4). Cox proportional hazards models, multivariable logistic regression models, and Kaplan–Meier analyses were used to evaluate the association between AMI and outcomes. Of 600 patients included, 115 had AMI (19.2%). AMI independently conferred an increased risk for major adverse cardiac events (adjusted hazard ratio, 1.69 [95% CI, 1.12–2.53]) and 90‐day unfavorable outcomes (adjusted odds ratio, 2.15 [95% CI, 1.26–3.67]) compared with patients without AMI. Conclusions AMI is relatively common in patients with intracerebral hemorrhage and is associated with both long‐term major adverse cardiac events and 90‐day unfavorable outcomes.